Enrollment and retention of female sex workers in HIV care in health facilities in Mbarara city - Arinaitwe, Bridget; Ariho, Philbert; Naturinda, Christine Hilda; Byoleko, Brian; Base, Anitah; Atwijukiire, Humphrey; Matavu, Hariat; Kabami, Jane; Obua, Celestine; Wakida, Edith K.; Otwine, Anne (Frontiers in Reproductive Health, 2023)
Background: Sex work is a global driver of the HIV epidemic and the risk of acquiring HIV is 13 times higher for female sex workers (FSW) compared to the general population this could be due to poverty, gender-based violence. The enrollment and retention of FSW into HIV care is a challenge, and has been a major contributing factor to increased new HIV infections Methods: We conducted a qualitative study among 30 female sex workers and 21 health workers working in ART clinics at the selected three primary health facilities in Mbarara City, Southwestern Uganda. The study participants were enrolled by both purposive and snowball sampling techniques. We obtained informed consent from all the participants and data was collected using in-depth interviews and thematically analyzed. Results: Three themes emerged as facilitators towards enrollment and retention of female sex workers into HIV care namely: 1) Good health living 2) Receptive health workers and availability of health services and 3) Community outreaches and peer support. The barriers are summarised into three major themes: 1) Stigma, community discrimination, and beliefs, 2) social obstacles 3) Adverse effects of ART, and 4) Inadequate services at the health facilities. Conclusion: Female sex workers are challenged by unsupportive environments and communities where they live and work, which hinders their enrolment and retention in HIV care. Creating awareness of the utilization of HIV care services and extending such services to hotspot communities could enhance the response of HIV-positive female sex workers to ART.